Taking on the doctor role in whole‐task simulation. (6th July 2017) - Bartlett, Maggie; Gay, Simon P; Kinston, Ruth; McKinley, Robert
Summary: Background: Untimed simulated primary care consultations focusing on safe and effective clinical outcomes were first introduced into undergraduate medical education in Otago, New Zealand, in 2004. We extended this concept and included a secondary care version for final‐year students. We offer students opportunities to manage entire consultations, which include making and implementing clinical decisions with simulated patients (SPs). Formative feedback is given by SPs on the achievement of pre‐determined outcomes and by faculty members on clinical decision making, medical record keeping and case presentation. Methods: We explored students' perceptions of the educational value of the sessions using post‐session questionnaires ( n  = 194) and focus groups ( n  = 36 participants overall). Students are offered opportunities to manage entire consultations with simulated patients Results: Students perceived that the sessions were useful, enjoyable and relevant to early postgraduate practice. They identified useful learning in time management, communication, decision making, prescribing and managing uncertainty. Students identified gaps in their knowledge and recognised that they had been offered opportunities to develop decision‐making skills by having to take responsibility for whole consultations and all the decisions included within them. Most students reported positive impacts on learning, although a small minority reported negative impacts on their perceptions of their ability to cope as a junior doctor. Discussion: These simulated consultation sessions appear to lead to the effective learning of a range of skills that students need in order to work as junior doctors. Facilitators leading such sessions must be alert to the possibility of educational harm arising from such simulations, and the need to address this during the debriefing.